From grey to green? Tipping a coal region incrementally - Mey, Franziska; Weik, Arno; Lilliestam, Johan (Global Environmental Change-Human and Policy Dimensions, 2024)
A rapid and full decarbonisation of both energy and industry is essential to meet the targets in the Paris agreement, which brings coal- and carbon-intensive regions under significant pressure. Some regions have advanced in their transition and can provide insights in the system change processes. In this paper, we investigate the socio-economic transition processes of Essen and Duisburg as part of the wider structural change in the Ruhr Region/ Germany. We explore causes and effects of their trajectories in the last 30 + years and identify differences in outcome as a function of the interventions and/or contextual differences, while investigating whether either city crossed a tipping point in their transition process (yet). Therefore, we specifically evaluate the cities’ development trajectories by seeking evidence for “no”, “incremental” or “radical or tipping” changes in sets of qualitative and quantitative indicators. Our analysis shows that both cities experienced incremental changes in their demographic, economic and political trajectories but we found no evidence for either city to have crossed a tipping point in their transition process yet. However, distinct developments in the cities’ policy narratives and visions indicate qualitative changes while putting them on different development trajectories potentially leading to tipping points in the future. Our study shows that the sequence of interventions and timing are important factors for the trajectory of a region determining the quality of societal change. It also suggests that radical change and tipping are the exception rather than the rule, especially in the highly complex social systems of cities.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Coal region; Coal-phase out; Incrementalism; Path dependency; Radical change; Social tipping points